2016
DOI: 10.1002/prca.201600003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and tyrosine nitration in traumatic brain injury: Insights into secondary injury from redox proteomics

Abstract: Traumatic brain injury (TBI) is a spontaneous event in which sudden trauma and secondary injury cause brain damage. Symptoms of TBI can range from mild to severe depending on extent of injury. The outcome can span from complete patient recovery to permanent memory loss and neurological decline. Currently, there is no known cure for TBI; however, immediate medical attention after injury is most beneficial for patient recovery. It is a well-established concept that imbalances in the production of reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…Meanwhile, SIRT1 is an important oxidative stress regulator (29). It is reported that TBI resulted in rapid ROS production and oxidative damage to brain cellular components leading to neuronal dysfunction and cell death (35). ROS is constantly generated and eliminated in the biological homoeostasis, which is controlled by endogenous antioxidant system, including antioxidants such as GSH and SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, SIRT1 is an important oxidative stress regulator (29). It is reported that TBI resulted in rapid ROS production and oxidative damage to brain cellular components leading to neuronal dysfunction and cell death (35). ROS is constantly generated and eliminated in the biological homoeostasis, which is controlled by endogenous antioxidant system, including antioxidants such as GSH and SOD.…”
Section: Discussionmentioning
confidence: 99%
“…So far, an heterogeneous group of polypeptides emerged as promising biomarkers for TBIs of different severities; this group includes structural proteins and enzymes reflecting either glial (S-100β, Tau proteins, GFAP, but also Rho-associated protein kinase 2 and carbonic anhydrase-I) or neuronal (peroxiredoxin-2, synaptosomal-associated protein 25, and microtubule-associated protein 1B) wellbeing or damage, depending on their variation from physiological range [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 41 , 42 , 43 , 44 , 45 ]. Since many neurological and behavioral abnormalities observed in patients with TBI may in fact be transient or permanent, and are the visible consequences of the cellular, sub-cellular, and molecular pathological processes and their evolution with time, investigations of animal models still result emphasize the paramount importance of approaching all of them in a more comprehensive way.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a well-known factor that exacerbates brain damage and neurological dysfunction due to its significant role in the etiology of progressive neuropathology in TBI [27][28][29][30][31][32] . The high metabolic demands on a reduced mitochondrial population as part of the secondary effects of TBI results in abundant ROS, which are the main source of oxidative stress in brain injuries [31] .…”
Section: Discussionmentioning
confidence: 99%